1998
DOI: 10.1002/hep.510280239
|View full text |Cite
|
Sign up to set email alerts
|

In situ detection of hepatitis B, C, and G virus nucleic acids in human hepatocellular carcinoma tissues from different geographic regions

Abstract: We performed a retrospective study to determine the prevalence of hepatitis B virus (HBV), hepatitis C virus (HCV), and hepatitis G virus (HGV) genomes in formalinfixed, paraffin-embedded liver tissues from hepatocellular carcinoma (HCC) patients in various geographic areas. Hepatocellular carcinoma (HCC) is increasing in incidence worldwide and is one of the most common malignant tumors in the world. It has been well documented that chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infections play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 35 publications
0
27
1
Order By: Relevance
“…The HBx protein is thought to play a major role in HCC by modifying apoptosis, inhibiting nucleotide excision and repair of damaged cellular DNA, and modulating transcriptional activation of cellular growth regulating genes [20]. Strong epidemiological evidence correlating HCC to HBV infection is demonstrated by the presence of HB surface antigen (HBs Ag) and HB core antibodies (HBc antibodies) in the blood of HCC patients [21]. Hepatocyte transformation may also be indirectly influenced by HBV DNA integration [22].…”
Section: Introductionmentioning
confidence: 99%
“…The HBx protein is thought to play a major role in HCC by modifying apoptosis, inhibiting nucleotide excision and repair of damaged cellular DNA, and modulating transcriptional activation of cellular growth regulating genes [20]. Strong epidemiological evidence correlating HCC to HBV infection is demonstrated by the presence of HB surface antigen (HBs Ag) and HB core antibodies (HBc antibodies) in the blood of HCC patients [21]. Hepatocyte transformation may also be indirectly influenced by HBV DNA integration [22].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in contrast to Western and Japanese studies, which report that the hepatitis C virus (HCV) is associated more frequently and is etiologically implicated with HCC than with HBV. 14,21,22 Active HBV vaccination programs are probably responsible for this change in viral prevalence in Japan both in HCC patients and in the general population. 2 Well differentiated HCCs are permissive to viral growth and replication as substantiated by a Korean study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, whether the liver is the replication site of HGV has remained unclear. Saito et al [32] had detected both positive and negative stranded HGV RNA by HGV RT-PCR in the liver tissues of all the six tested HGV infected patients, which indicated that liver might be the primary site of HGV replicatio n, but many other scientists could not repeat these findings in their HGV infected patients by the same METHODS [33][34][35][36] . Recently, Reshetnyak et al reported that patients with HGV monoinfection had demonstrated the increase of the DNA single-stranded breaks peripheral blood lymphocytes (PBL) quantity [37] .…”
Section: Discussionmentioning
confidence: 99%